Antibacterial mechanisms of magnolol against Streptococcus agalactiae and immunomodulatory effects in Schizothorax prenanti - Yilin Wang; Kun Peng; Longjun Deng; Yihao Wang; Qibin Jiang; Tiancai Li; Ping Ouyang; Defang Chen; Xiaoli Huang; Yi Geng (Fish & Shellfish Immunology, 2026)

Travel-Time Transformer Residual U-Net for sparse first-arrival imaging of low-velocity anomalies - Longjun Dong; Zhongjie Chen; Zhongwei Pei; Longbin Yang (Journal of Applied Geophysics, 2026)

Genome-Guided Probiotic Mechanisms of Enterococcus hirae SMU2502: Wnt/β-catenin-Driven Intestinal Epithelial Proliferation and Protection Against Salmonella Infection - Longjun Ran; Danni Wang; Haojinming Tang; Ganlin Wang; Wenzhu Salang; Falong Yang; Huanrong Zhang; Haifeng Liu; Shiwen Xu; Dechun Chen (Probiotics and Antimicrobial Proteins, 2026)

Life-cycle regulation of carbohydrate metabolism revealed by glucokinase (gck) in two cyprinids, Spinibarbus denticulatus and Schizothorax prenanti - Yongyao Guo; Yue Zhang; Tiancai Li; Longjun Deng; Zhonggang Guo; Li Liu; Pengyu Chen; Luojia Li; Wei Luo; Dongjie Wang; Zongjun Du (Aquaculture, 2026)

Wake-induced vibration of a downstream cylinder in tandem configurations: an activation-modulation framework - Qiuying Li; Guanghao Chen; Nan Jiang; Jinhui Yue; Longjun Wang; Jian Liu (Ocean Engineering, 2026)

Presymbiotic activation of karrikin signaling creates a permissive state for arbuscular mycorrhizal symbiosis by derepressing the NSP1–NSP2–SLR1 transcriptional complex in rice - Kai Hong; Xueying Yang; Yiqing Tan; Yonggang Liu; Qianwei Xia; Longjun Zeng; Linyuan Zou; Ke Wan; Ya Zhang; Shujing Kang; Tao Huang; Wanqing Lv; et al. (Molecular Plant, 2026)

Responses of viral communities and viral-encoded auxiliary metabolic genes to long-term fertilization practices under different land-use types - Xunqi Chen; Dong Zhu; Yuling Zheng; Xiaomin Li; Guoxin Sun; Xiaoming Li; Longjun Ding (Journal of Environmental Sciences, 2026)

Measurement and Impact Mechanism of Carbon Costs in China’s Industrial Enterprises - Liping Wang; Longjun Chen; Panpan Gao; Chuang Li (Environmental Modeling & Assessment, 2026)

Cyclic Impact-Induced Dynamic Responses and the Rockbolt Slippage Mechanism of a Prestressed Rock-Like Anchorage System - Qiuhong Wu; Hao Xiao; Lei Weng; Longjun Dong; Yanlin Zhao; Zhenghong Chen; Wuxing Wu; Zhili Peng (Rock Mechanics and Rock Engineering, 2026)

Dual-Path valorization of organic waste via black soldier fly: Synergistic enhancement of feed efficiency, crop quality, and climate mitigation in closed-loop aquaculture - Longjun Chen; Yu Lin; Xianbo Jia; Xiangzhou Zheng; Yuchen Zhuo; QianQian Chen; Haiping Fan; Yu Fang; Hui Zhang; Chenqiang Lin (Waste Management, 2026)

Biochar-Amended Composting Transforms Chicken Manure Waste Into a Resource: Enhancing Extra-Rhizosphere Soil Fertility and Shaping Microbial Communities - Longjun Chen; Haiping Fan; Lulong Zhong; Yuncai Wang; Cheng Chen; Xin Chen; Yanping Chen; Jiaolin Zhang; Yu Lin (Journal of Soil Science and Plant Nutrition, 2025)
This study elucidates the synergistic regulatory mechanisms of biochar-amended chicken manure and mushroom residue compost (BCM) on soil microbial communities and nutrient cycling in the extra-rhizosphere, while evaluating its potential for sustainable agricultural waste recycling. Methods: We conducted a 50-day composting trial using five biochar application rates (0–7%). Assessed parameters included compost maturity (C/N ratio), nutrient content (NO 3 − -N, available phosphorus [AP], soil organic matter [SOM]), phosphatase and catalase activities, microbial community composition, and metabolic pathways. We performed Redundancy analysis (RDA) to correlate SOM/AP dynamics with microbial diversity and functional pathways. Results: At 5–7% biochar, compost maturity improved significantly, with C/N ratios of 15.6–18.2 and 2.2-4.0-fold increases in NO 3 − -N (1.41 mg/g), AP (50.09 mg/kg), and SOM (166.11 g/kg). Enzymatic activities (phosphatase: 9.81 mg/g·24 h; catalase: 83.08 µmol/g·24 h) correlated strongly with SOM/AP (R 2 = 0.71–0.82). Biochar enriched Proteobacteria (34.1%) and Actinobacteriota (15.2%), suppressed Halophiles ( Halomonas reduced by 52%), and enhanced carbon metabolism and oxidative phosphorylation pathways. RDA identified SOM/AP as a key driver of microbial diversity (R 2 = 0.91). The 5% biochar dose optimized nutrient retention (37–59% increases in AP, Available potassium [AK], NO 3 − -N) while maintaining microbial diversity, outperforming higher doses. Conclusions: This study demonstrates biochar’s dual role in reshaping extra-rhizosphere microbial ecology and nutrient dynamics, offering a precision agriculture strategy for sustainable waste recycling and circular economy practices. The 5% biochar dosage proved optimal, enhancing nutrient cycling and microbial activity while mitigating halophilic microbial suppression. Graphical Abstract

How to improve enterprises’ responsiveness to green policies? Empirical evidence from multivariate policy scenario analysis - Liping Wang; Longjun Chen; Ting Zeng; Chuang Li (Environment, Development and Sustainability, 2025)

Knockout of the Staphylococcus aureus virulence gene sdrC promotes Myh7 expression to inhibit the progression of osteomyelitis - Baochuang Qi; Lili Yang; Xinyu Fan; Dongdong Qin; Jiming Gan; Tao Chen; Yu Rao; Zhongyu Peng; Longjun Su; Chuan Li; Yongqing Xu (Journal of Molecular Histology, 2025)

Golgi apparatus regulated pyroptosis through the miR-32-5p/Golga7/NLRP3 axis in chicken splenic lymphocytes exposure to ammonia - Jiahao Liu; Haifeng Liu; Haojinming Tang; Longjun Ran; Danni Wang; Falong Yang; Huanrong Zhang; Xiaohua Teng; Dechun Chen (Environmental Pollution, 2024)

A Novel Disturbance Stress Direction Identification Method of Rock Mass Using Acoustic Parameters - Yongchao Chen; Jiang Guo; Longjun Dong (Rock Mechanics and Rock Engineering, 2024)

Spatio-temporal evolution characteristics and spatial spillover effects of forest carbon sink efficiency in China - Liping Wang; Longjun Chen; Ying Long; Chuang Li (Environment, Development and Sustainability, 2024)

A novel ZnCo2O4/BiOBr p-n/Z-scheme heterojunction photocatalyst for enhancing photocatalytic activity - Tao Xiong; Qi Feng; Cimei Fang; Rui Chen; Yanxi Wang; Longjun Xu; Chenglun Liu (Environmental Science and Pollution Research, 2024)

Genotype diversity and antibiotic resistance risk in Aeromonas hydrophila in Sichuan, China - Kun Peng; Mengzhu Chen; Yilin Wang; Ziqi Tian; Longjun Deng; Tiancai Li; Yang Feng; Ping Ouyang; Xiaoli Huang; Defang Chen; Yi Geng (Brazilian Journal of Microbiology, 2024)

miRNA-146a-5p Inhibits Hypoxia-Induced Myocardial Fibrosis Through EndMT - Yan Wang; Jie Yu; Chunxia Ou; Yue Zhao; Lixing Chen; Wenke Cai; Huawei Wang; Shiying Huang; Jie Hu; Guihu Sun; Longjun Li (Cardiovascular Toxicology, 2024)

IFITM3 restricts porcine deltacoronavirus infection by targeting its Spike protein - Jianxiao Wu; Rongfeng Tang; Xiaorong Zhang; Mingzhe Gao; Longjun Guo; Liaoyuan Zhang; Da Shi; Xin Zhang; Hongyan Shi; Hongying Song; Li Feng; Jianfei Chen (Veterinary Microbiology, 2024)

Gill structure and respiratory ability of Euchiloglanis kishinouyei (Osteichthyes: Siluriformes: Sisoridae) - Luojia Li; Longjun Deng; Jie Li; Tiancai Li; Pengyu Chen; Wei Luo; Zongjun Du (Journal of Fish Biology, 2023)
Glyptosternoid fishes are distributed in the torrent environment of alpine canyons, where they often leave the water to climb rocky cliffs. As one of the most primitive species of glyptosternoid fishes, Euchiloglanis kishinouyei was examined in the current study to analyse its gill microstructure and respiratory ability. We first found that the oxygen consumption rate was relatively high and negatively correlated with body mass and that the average oxygen consumption at night was higher than during the day. The asphyxiation point of E. kishinouyei (5.05 ± 0.22 g) was c . 1.93 mg/L. Subsequently, the surface morphology, gross gill tissue structure, and ultra‐microstructure of gill lamellae were investigated using optical microscopy and SEM. The gills showed an overall trend of regression, with five pairs of gill arches in each gill cavity. The adjacent gill filaments had large gaps, and the gill lamellae were thick. The gill filaments were closely arranged on the gill arches, their folded respiratory surface was highly vascularized with no tiny crest, and there were obvious tiny crests, grooves, pits, and pores on the nonrespiratory surface. The gill lamellae were closely embedded on both sides of gill filaments, which were composed of flat epithelial cells, basement membrane, pillar cells, and mucous cells. The gill total respiratory area correlated positively with body mass and length, whereas the gill relative respiratory area correlated negatively with body mass. We comprehensively analysed the gill microstructure and respiratory capacity of E. kishinouyei to provide fundamental data for the adaptive evolution of the gill structures of bimodally respiring fishes and offer insights into further study on the accessory air‐breathing function of skin.

The gravitational potential and its first- and second-order partial derivatives of an ellipsoidal tesseroid based on the Cartesian integral kernel - Shuai Wang; Zhaoxi Chen; Longjun Qiu (Studia Geophysica et Geodaetica, 2023)

Visualization and metabolome for the migration and distribution behavior of pesticides residue in after-ripening of banana - Meiran Wang; Qiaoxia Tian; Hongxing Li; Longjun Dai; Yi Wan; Mingyue Wang; Bingjun Han; Huaping Huang; Yunuo Zhang; Juncheng Chen (Journal of Hazardous Materials, 2023)

Acoustic Emission Location Accuracy and Spatial Evolution Characteristics of Granite Fracture in Complex Stress Conditions - Longjun Dong; Longbin Yang; Yongchao Chen (Rock Mechanics and Rock Engineering, 2023)

Degradation of poly(butylene adipate-co-terephthalate) films by Thermobifida fusca FXJ-1 isolated from compost - Xianbo Jia; Ke Zhao; Jie Zhao; Chenqiang Lin; Hui Zhang; Longjun Chen; Jichen Chen; Yu Fang (Journal of Hazardous Materials, 2023)

Comparative transcriptome and adaptive evolution analysis on the main liver and attaching liver of Pareuchiloglanis macrotrema - Qing Wu; Xiaoyang Zhang; Jie Li; Longjun Deng; Dongjie Wang; Min Liao; Zhonggang Guo; Xiaoli Huang; Defang Chen; Yan Wang; Shiyong Yang; Zongjun Du; et al. (Journal of Applied Genetics, 2022)

Easy detection for the high-pass filter cut-off frequency of digital ground motion record based on STA/LTA method: a case study in the 2008 Wenchuan mainshock - Xu Longjun; Chen Yabin (Journal of Seismology, 2021)

Comparison of three methods for computing the gravitational attraction of tesseroids at satellite altitude - Longjun Qiu; Zhaoxi Chen (Studia Geophysica et Geodaetica, 2021)

Gravity field of a tesseroid by variable-order Gauss–Legendre quadrature - Longjun Qiu; Zhaoxi Chen (Journal of Geodesy, 2020)

Construction of Stress Responsive Synthetic Promoters and Analysis of Their Activity in Transgenic Arabidopsis thaliana - Lei Hou; Longjun Chen; Junyi Wang; Dongfang Xu; Lixin Dai; Hui Zhang; Yanxiu Zhao (Plant Molecular Biology Reporter, 2012)

Carbonate mineral saturation states along the U.S. East Coast - Li-Qing Jiang; Wei-Jun Cai; Richard A. Feely; Yongchen Wang; Xianghui Guo; Dwight K. Gledhill; Xinping Hu; Felipe Arzayus; Feizhou Chen; Justin Hartmann; Longjun Zhang (Limnology and Oceanography, 2010)
To assess the impact of ocean acidification on the carbonate chemistry of the shelf waters off the southeastern United States (South Atlantic Bight [SAB]), we measured carbonate mineral saturation states from January 2005 to May 2006. The findings reveal that aragonite (Ω arag : 2.6–4.0) and calcite (Ω cal : 4.1–6.0) saturation states were considerably higher than those recently reported along the West Coast of North America. Different water mass age between the Atlantic and Pacific Oceans during global ocean circulation is the primary reason for the higher carbonate mineral saturation states in the SAB than along the West Coast. The contrasting water temperatures in the two coasts contribute to such differences. Both upwelling and freshwater discharge also play important roles in controlling saturation state. Carbonate mineral saturation in the surface water of the West Coast is strongly controlled by the upwelling of high‐salinity, low‐temperature, low‐oxygen, and low‐pH deep water. In comparison, saturation states in the surface water of the SAB coast are rarely affected by upwelling. Instead, they are strongly influenced by the input of low‐saturation‐state water from rivers. Continued increases of atmospheric CO 2 under the Intergovernmental Panel on Climate Change B1 emission scenario will decrease the carbonate mineral saturation states by up to 40% by the end of this century, and aragonite will approach undersaturation near the coast.